2020
DOI: 10.18632/oncotarget.27414
|View full text |Cite
|
Sign up to set email alerts
|

Novel functional anti-HER3 monoclonal antibodies with potent anti-cancer effects on various human epithelial cancers

Abstract: Copyright: Okita et al. This is an open-access article distributed under the terms of the Creative Commons Attribution License 3.0 (CC BY 3.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited. ABSTRACTResistance of progressive cancers against chemotherapy is a serious clinical problem. In this context, human epidermal growth factor receptor 3 (HER3) can play important roles in drug resistance to HER1-and HER2-targeted therapies.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 52 publications
(67 reference statements)
0
13
0
Order By: Relevance
“…However, previous clinical studies showed that blocking HER3 had limited anti-tumor effect in several types of cancer by using either HER3 antibodies/inhibitors as monotherapies or in combination with EGFR-or HER2-targeted therapies such as cexucimab and trastuzumab [48][49][50] . The HER3 antibody used in this study, seribantumab, has been used in clinical studies for treating breast, lung, and ovarian cancer either alone or in combination with paclitaxel or EGFR/HER2 targeted therapies [51][52][53] .…”
Section: Discussionmentioning
confidence: 99%
“…However, previous clinical studies showed that blocking HER3 had limited anti-tumor effect in several types of cancer by using either HER3 antibodies/inhibitors as monotherapies or in combination with EGFR-or HER2-targeted therapies such as cexucimab and trastuzumab [48][49][50] . The HER3 antibody used in this study, seribantumab, has been used in clinical studies for treating breast, lung, and ovarian cancer either alone or in combination with paclitaxel or EGFR/HER2 targeted therapies [51][52][53] .…”
Section: Discussionmentioning
confidence: 99%
“…KO was performed as recently described [ 51 , 52 ] using pX330 and pCAG-EGxxFP [ 53 ] purchased from Addgene (Watertown, MA, USA). For CRISPR/Cas9-based CD98hc (SLC3A2) gene disruption, guide (g) RNA sequences (5′-GCCGCGTTGTCGCGAGCTAC-3′) corresponding to the CD98hc gene (318-bp ~ 337-bp from the initiation ATG site) were designed using CRISPR direct ( https://crispr.dbcls.jp/ ).…”
Section: Methodsmentioning
confidence: 99%
“…Aseptic processing during cell culture was ideally controlled by a MediAir air purifier (Pieras Co., Ltd) equipped in the cell‐culture room. Cell growth was measured as previously described 13 . Briefly, a WST‐8–based cell counting kit (Dojin Chemicals) was used, and 450 nm was measured using a microplate reader.…”
Section: Methodsmentioning
confidence: 99%
“…Cell growth was measured as previously described. 13 Briefly, a WST-8-based cell counting kit (Dojin Chemicals) was used, and 450 nm was measured using a microplate reader.…”
Section: Cell Culturementioning
confidence: 99%
See 1 more Smart Citation